Aplicação pré-colheita de reguladores de crescimento na qualidade e fisiologia pós-colheita de caju - Souza, Kellina Oliveira de (2016)
Cashew apple, no climacteric fruit, has great prominence in the Brazilian fruit sector, as it represents an economic and social activity of great expression in the Northeast, totally must be harvested ripe and being highly perishable, technologies pre-harvest can assist in their conservation post sampling, maintaining the firmness and shelf life. One of the problems faced by farmers, especially those facing fresh Cashew apples consumption, is its rapid maturation in the plant, which makes the marketing of this product. Therefore, the use of technologies for extending the harvest period and promote the maintenance of peduncles quality postharvest are needed. Thus, plant growth regulators such as gibberellins (GA3) and aminoethoxyvinylglycine (AVG), have been used as a treatment for maintaining the fruit postharvest quality. The aim of this study was to evaluate the effect of pre-harvest application of gibberellic acid (GA 3, ProGibb®) and aminoethoxyvinilglycine (AVG, ReTain®) on the quality and postharvest shelf life of peduncles of two clone’s cashew tree (CCP 76 and BRS 189) for storage at 3 and 5 ± 2 °C, respectively. The application of both regulators, GA3 (180 mg L-1) and AVG (180 mg L-1) occurred 40 days after anthensis, stage in which the fruits had brown and green coloring of peduncle. The fruits were harvested 5 days after treatment application, the commercial harvest point. The data presented here demonstrate that the effects of GA3 pre-harvest treatment improved clone’s peduncle postharvest quality by reducing the weight loss and maintenance of firmness during refrigerated storage. The effects of AVG on the quality and peduncle physiology were inconsistent.